Degradation of PAHs by ligninolytic enzymes of Irpex lacteus - Cajthaml, T; Erbanová, P; Kollmann, A; Novotný, C; Sasek, V; Mougin, C (Folia microbiologica, 2008)
The ligninolytic fungus Irpex lacteus was shown as an efficient degrader of oligocyclic aromatic hydrocarbons (PAHs; 'polycyclic aromatic hydrocarbons') possessing 3-6 aromatic rings in complex liquid media. The strain produced mainly Mn-dependent peroxidase in media without pollutants. Activity of ligninolytic enzymes was higher in a N-limited medium. However, after contamination with PAHs (especially pyrene) the values increased and significant activity of Mn-independent peroxidase appeared in the complex medium. Other factors (such as the increase in nitrogen concentration or the presence of solvent(s) for dissolution of PAHs) had no effect. Cytochrome P-450 was detected in the microsomal fraction of biomass grown in the complex medium. The rate of PAH degradation was also affected by the presence of various combinations of PAHs. However, independently of the enzyme activities, anthracene was shown to have a positive influence on degradation of pyrene and fluoranthene.
Keywords: Polycyclic Aromatic Hydrocarbons; lignin; Lignin; Basidiomycota; peroxidasy; polycyklické aromatické uhlovodíky; fungální proteiny; biodegradace; Fungal Proteins; Biodegradation, Environmental; Peroxidases